Identification and fine-mapping of a major QTL (PH1.1) conferring plant height in broomcorn millet (Panicum miliaceum) - Liu, Tianpeng; Liu, Xueying; He, Jihong; Dong, Kongjun; Pan, Wanxiang; Zhang, Lei; Ren, Ruiyu; Zhang, Zhengsheng; Yang, Tianyu (Frontiers in Plant Science, 2022)
The plant height of broomcorn millet (Panicum miliaceum) is a significant agronomic trait that is closely related to its plant architecture, lodging resistance, and final yield. However, the genes underlying the regulation of plant height in broomcorn millet are rarely reported. Here, an F2 population derived from a cross between a normal variety, “Longmi12,” and a dwarf mutant, “Zhang778,” was constructed. Genetic analysis for the F2 and F2:3 populations revealed that the plant height was controlled by more than one locus. A major quantitative trait locus (QTL), PH1.1, was preliminarily identified in chromosome 1 using bulked segregant analysis sequencing (BSA-seq). PH1.1 was fine-mapped to a 109-kb genomic region with 15 genes using a high-density map. Among them, longmi011482 and longmi011489, containing nonsynonymous variations in their coding regions, and longmi011496, covering multiple insertion/deletion sequences in the promoter regions, may be possible candidate genes for PH1.1. Three diagnostic markers closely linked to PH1.1 were developed to validate the PH1.1 region in broomcorn millet germplasm. These findings laid the foundation for further understanding of the molecular mechanism of plant height regulation in broomcorn millet and are also beneficial to the breeding program for developing new varieties with optimal height.